الاساليب النبوية لحل المشكلات الأسرية: Prophetic Traditions for the Solution of Domestic Disputes (Al-Qamar, 2023)
Marriage is the basic unit of a human society. It is a social institution in which a male and a female both are bound to live together while having their own domains of rights and responsibilities. According to Islam “Marriage” is a religious duty, a moral safeguard and a social commitment .Married life cannot be considered without conflicts and these conflicts can differ according to nature and intensity of the issues. Sometimes the main reason behind these disputes are just the ignorance and negligence from the provisions of marriage contract .So if these rules are provisions are known and applied, then family system is upright and its structure remains coherent. Likewise was the house of Prophet Muhammad PBUH. He was best among the human being and was innocent but His wives were not among the angels. So if some dispute occurred he was used to resolve it from his God gifted wisdom and understanding. In this article some of his Prophetic ways and techniques are discussed to resolve the domestic conflicts.
Keywords: Domestic; Dispute; Prophetic Ways; Resolve; Solution